Evaluasi Kesesuaian Dosis pada Pasien Pediatri Bronkitis Akut di Rumah Sakit Tentara Kartika Husada Kubu Raya - Kharis, Variandini Aldhila; Desnita, Rise; IH, Hariyanto (Pharmaceutical Sciences and Research, 2018)
Selection and usage of rational drugs determine the success of expected therapeutic effect, especially for pediatrics. Acute bronchitis in pediatrics is one of the highest incidents of Acute Respiratory Infection (ARI) in Army Hospital Kartika Husada Kubu Raya. This study aimed to evaluate rationality of drug doses conformity in outpatient pediatric acute bronchitis in Army Hospital Kartika Husada Kubu Raya on 2015. This research was a descriptive observational research with cross-sectional design. The sample was taken with purposive sampling amounted to 36 prescriptions. Then the evaluation of drug doses conformity was counted according to the literature. The results showed that drugs which were used for acute bronchitis were mucolitics and expectorants, antibiotics, bronchodilators, multivitamins, decongestans, analgesics, and antihistamins. The result of drug dosage conformity evaluation showed that the under-dose drug item (R/) was 51%, over-dose was 15% and appropriate dose was 34%.